Materialization of novel composite bio‐based active edible film functionalized with essential oils on antimicrobial and antioxidative aspect of chicken nuggets during extended storage. Issue 9 (18th August 2020) - Bharti, Sanjay Kumar; Pathak, Vikas; Alam, Tanweer; Arya, Anita; Singh, Vinod Kumar; Verma, Arun Kumar; Rajkumar, Vincentraju
Abstract : Abstract: The present study was aimed to develop Manihot esculenta and Carrageenan bio‐based composite active film functionalized with anise, caraway, and nutmeg essential oils (EOs) and to assess the shelf life of chicken nuggets wrapped with the developed film at refrigeration storage. Overall, the Minimum Inhibitory Concentration (MIC) values of the three EOs ranged from 0.4 to 0.8% v/v of which nutmeg EO was found most effective. Incorporation of EOs in the film resulted in significant ( P ˂ 0.05) decrease in tensile strength and water activity while elongation at break was significantly ( P ˂ 0.05) increased. No significant ( P ˃ 0.05) changes in thickness and Water Vapor Transmission Rate (WVTR) were observed. Based on physicomechanical and sensory evaluation, films incorporated with 0.5, 1, and 1% concentration of anise, nutmeg, and caraway EO were selected. Chicken nuggets overwrapped with aforementioned films were stored aerobically at refrigeration temperature (4 ± 1 °C) to evaluate antimicrobial, antioxidant, and sensory characteristics. The result indicated that pH, peroxide, free fatty acid (FFA), and thiobarbituric acide (TBA) value of treatments were significantly ( P ˂ 0.05) lower than controls however significantly ( P < 0.05) higher DPPH activity was observed in all treatments. The total plate count, psychrophilic count and, yeast and mold count were also significantly ( P ˂ 0.01) lower in treatment groups and were within the permissible limits. The treated samples were well acceptable during whole storage period of 15 days. The application of composite, active edible bio‐based film was found proficient in confining product quality attributes throughout storage. Practical Application: The majority of films used for packaging of meat and meat products are derived from synthetic "plastic" materials. The demerits associated with plastics have eventually led to explore natural alternatives such as edible films. The composite‐active bio‐based films have a huge potential to be molded for specific film properties based on requirements of product‐specific packaging conditions.